2021
DOI: 10.7189/jogh.11.04048
|View full text |Cite
|
Sign up to set email alerts
|

Causes of maternal mortality in Sub-Saharan Africa: A systematic review of studies published from 2015 to 2020

Abstract: Background Maternal deaths remain high in Sub-Saharan Africa (SSA) and their causes of maternal death must be analysed frequently in this region to guide interventions. Methods We conducted a systematic review of studies published from 2015 to 2020 that reported the causes of maternal deaths in 57 SSA countries. The objective was to identify the leading causes of maternal deaths using the international classification of disease – 10 th revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 60 publications
2
79
1
1
Order By: Relevance
“…In this study, we shall take a special look at the four human development factors (i.e., education, infrastructure, sanitation, and health frameworks) recommended in many studies [ 10 14 ], which are pivotal for success in decreasing MMR substantially. A comparison shall be made between countries of India and Bangladesh with Rwanda, and analysis shall be done, to see how Rwanda fares against these two.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we shall take a special look at the four human development factors (i.e., education, infrastructure, sanitation, and health frameworks) recommended in many studies [ 10 14 ], which are pivotal for success in decreasing MMR substantially. A comparison shall be made between countries of India and Bangladesh with Rwanda, and analysis shall be done, to see how Rwanda fares against these two.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, this research is aimed at studying the current state of maternal mortality rate in Rwanda and the factors behind its performance, in a comparative study with India and Bangladesh which have been able to perform very well in decreasing MMR for the adult female populations. The choice of variables used in this study resulted from the review of the literature and as a result pivotal indicators or factors that affect healthcare are shortlisted, and we have identified country's economy represented by GDP per capita, health expenditure per capita, government commitment, female literacy rate, healthcare infrastructure and improvement in sanitation, sanitation facilities, and presence of nurses and midwives as commendable studies recommend these factors as building blocks contributing to maternal health [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa (SSA), several countries have reported a significant improvement in the utilisation of ANC services by pregnant women, yet the maternal and neonatal morbidity and mortality has remained unacceptably high [ 7 , 9 ]. Adequate and quality ANC has been documented to contribute towards reduction of maternal and neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Health related factors found to be statistically associated with access to other health services in our study were hypertension and mental health risk. Previous research has shown that hypertension is one of the top three leading causes of maternal mortality in sub-Saharan Africa ( 24 ). Therefore, active follow up and improved access to health care by hypertensive mothers would have a positive impact on their health.…”
Section: Discussionmentioning
confidence: 99%